Creator Of the Universe Adjusted the Dark Energy/Dark Matter Ratio and Baryons to Be Function In Π And Eπ: Predicted and Deciphered by Sayeed’s Theorem - El-Mongy, Sayed Ali (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The fine tuning of the universe was adjusted by Allah – the Creator. This article deciphered the dark energy (DE), dark matter (DM) and baryonic matter (BM) pattern ambiguity as a one of the physics mysteries. In this article and for the first time, the ratio of the dark energy/dark matter and baryons are predicted by Sayed`s theorem to be function in π and eπ. The previous published measurements and estimations have been showing different values and variations. It is predicted that the ideal and optimum (DE/DM) ratio is equal to the constant π; called Sayed El-mongy (DE/DM) ratio; symbolized as (sAM). While, the ratio (DE/DM+BM) is to the constant e. The value of (DE/DM) multiplied by (DE/DM+BM) was found to be eπ. The typical predicted values of dark energy, dark matter and baryons are 71.314093%, 22.7% and 3.538% respectively. The remainder 2.450907% could be due to undiscovered and any other form of matter (OM) including neutrinos and antimatter. The comparison of the predicted values with the world range and published data was also carried out and given with the % discrepancy. It was observed that the closest values to the predicted (DE/DM) Sayed ratio (π) are with the difference of 0.35508198% for SWIN and 1.02083609% for WAMP respectively.